2016
DOI: 10.1007/s00299-016-2016-9
|View full text |Cite
|
Sign up to set email alerts
|

Significant increase of oleic acid level in the wild species Lepidium campestre through direct gene silencing

Abstract: Simultaneous RNAi silencing of the FAD2 and FAE1 genes in the wild species Lepidium campestre improved the oil quality with 80 % oleic acid content compared to 11 % in wildtype. Field cress (Lepidium campestre) is a wild biennial species within the Brassicaceae family with desirable agronomic traits, thus being a good candidate for domestication into a new oilseed and catch crop. However, it has agronomic traits that need to be improved before it can become an economically viable species. One of such traits is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…For example, the silencing of different genes (namely LABA1 and RAE2) via RNA interference has been used to shorten the awns of a rice introgression with long barber awns (Hua et al, 2015;Bessho-Uehara et al, 2016). Similarly, the silencing of genes of fatty acid biosynthesis (FAD2 and FAE1) improved the seed oil quality of the wild plant field cress (Lepidum campestre) (Ivarson et al, 2016). Mimicry of domestication has additionally been achieved by random mutagenesis followed by sequence evaluation of the ''targeted'' domestication gene.…”
Section: De Novo Domesticationmentioning
confidence: 99%
“…For example, the silencing of different genes (namely LABA1 and RAE2) via RNA interference has been used to shorten the awns of a rice introgression with long barber awns (Hua et al, 2015;Bessho-Uehara et al, 2016). Similarly, the silencing of genes of fatty acid biosynthesis (FAD2 and FAE1) improved the seed oil quality of the wild plant field cress (Lepidum campestre) (Ivarson et al, 2016). Mimicry of domestication has additionally been achieved by random mutagenesis followed by sequence evaluation of the ''targeted'' domestication gene.…”
Section: De Novo Domesticationmentioning
confidence: 99%
“…Much of the natural variation in seed oil composition in Arabidopsis has been attributed to FAD2 and FAE1 [ 74 ]. Indeed, downregulation of FAD2 and FAE1 in field cress also results in altered oil composition, drastically increasing the proportion of desirable oleic acid in the oil [ 75 ]. All the five genes shared high homology to the Arabidopsis orthologs and nonsynonymous polymorphisms were observed in FAD2 , KCS8 and WRI1 .…”
Section: Discussionmentioning
confidence: 99%
“…The primer pairs for the AtWRI1, AtHb2 , and BvHb2 genes (Supplementary Table S1) were chosen among several pairs tested for their efficiency and specificity. The TIP41-like reference gene (Supplementary Table S1) was used as a reliable reference in this study as reported by Lenser and Theissen (2013), Muhlhausen et al (2013), and Ivarson et al (2016). For each line, three biological replicates and three technical replicates were conducted.…”
Section: Methodsmentioning
confidence: 99%
“…The oxidative and temperature stable oleic acid was increased from around 10% in the wild type (WT) to over 80% in the transgenic lines. Furthermore, the level of erucic acid was decreased from over 20% down to 0.2% (Ivarson et al, 2016). …”
Section: Introductionmentioning
confidence: 99%